(untitled) (Significação: Journal of Audiovisual Culture, 2015)
Discussions on sound design in cinema go beyond the issue of sound-image synchronization. An example is !lmmaker Lucrécia Martel’s use and elaboration of the soundtrack - mainly in works such as La ciénaga (The Swamp, 2001) and La mujer sin cabeza (The Headless Woman, 2008) -, which establishes a different kind of observation in relation to the space constructed by the soundtrack and evidences other possible readings of the movie. As much as Martel’s work with narrative spaces through sound is unique and bold, emphasizing the importance and the possibility of using this element in the composition of the staging space and in the relationship with the mise en scène, two examples in Brazilian contemporary cinema - Kleber Mendonça Filho’s O som ao redor (Neighboring Sounds, 2013) and Marcelo Lordello’s Eles voltam (They’ll Come Back, 2014) stand out for their use of the soundtrack. Based on the creation of soundscapes that surround the characters, the movies subtly build the concepts of alterity and identity, weaving an interesting interplay of differences and similarities between what is seen (identity) and what is heard (alterity).